2016
DOI: 10.1186/s13071-016-1582-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic potential of urinary N-Acetyltyramine-O,β-glucuronide (NATOG) as diagnostic biomarker for Onchocerca volvulus infection

Abstract: BackgroundOnchocerciasis, also known as river blindness is one of the neglected tropical diseases affecting millions of people, mainly in sub-Saharan Africa and is caused by the filarial nematode Onchocerca volvulus. Efforts to eliminate this disease are ongoing and are based on mass drug administration programs with the microfilaricide ivermectin. In order to monitor the efficacy of these programs, there is an unmet need for diagnostic tools capable of identifying infected patients. We have investigated the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…While 89% of these samples were MF-negative, which supports successful ivermectin treatment. In support of this, the reported NATOG values in the study from Lagatie et al were in the range of our O. volvulus -negative control samples (including 51 samples collected from patients infected with Lymphatic filariasis ) 34 . Moreover, these results parallel our published NATOG values stemming from samples containing combined ivermectin and doxycycline-treatment 10 .…”
supporting
confidence: 89%
See 1 more Smart Citation
“…While 89% of these samples were MF-negative, which supports successful ivermectin treatment. In support of this, the reported NATOG values in the study from Lagatie et al were in the range of our O. volvulus -negative control samples (including 51 samples collected from patients infected with Lymphatic filariasis ) 34 . Moreover, these results parallel our published NATOG values stemming from samples containing combined ivermectin and doxycycline-treatment 10 .…”
supporting
confidence: 89%
“…Thus, from the Lagatie study samples were determined to be O. volvulus -positive based upon nodule palpitation. Using this as their initial metric MF-counting of these nodule-positive samples presented low MF-counts (99% below 5 MF/mg) 34 . While 89% of these samples were MF-negative, which supports successful ivermectin treatment.…”
mentioning
confidence: 63%
“…Another promising approach was the LC-MS based metabolomics analysis of serum [17] or urine [18] of Ov-infected individuals. Though the latter study identified N-acetyltyramine-O,β- glucuronide (NATOG) as a potential unique marker for onchocerciasis in humans [17, 18] and shown to be detectable before the onset of microfilariae in jirds infected with L. sigmodontis [19], its applicability has been questioned as the presence of NATOG failed to differentiate nodulepositive but amicrofilaraemic individuals from control groups [20]. …”
Section: Introductionmentioning
confidence: 99%
“…NATOG concentrations were determined in urine samples by liquid chromatography tandem mass spectrometry (LC-MS/MS) at Janssen Global Public Health (Beerse, Belgium), as described earlier [12]. Quality control and calibration samples were prepared as described before [12] and a standard curve (1-100 µM) was constructed by spiking stock solutions of NATOG to 25-fold diluted urine. The LOQ was defined at 0.7 µM.…”
Section: Mass Spectrometry Analysismentioning
confidence: 99%
“…NATOG is the inactivated form of the O. volvulus neurotransmitter tyramine, which is excreted in the urine of infected individuals [9,10]. Since the discovery of NATOG, several studies have tried to determine a cut-off value for urinary NATOG concentration to diagnose active O. volvulus infection [9][10][11][12]. However, the results of these studies are conflicting.…”
Section: Introductionmentioning
confidence: 99%